QUO VADIS: LEGAL CERTAINTY OF INFORMAL WORKER THROUGH MANPOWER ACT - Muhammad Prasetyo Wicaksono; Retno Rusdjijati; Nia Kurniati Bachtiar; Hary Abdul Hakim; Chrisna Bagus Edhita Praja (Jurnal Cendekia Hukum, 2023)
Issue related to legal protection policies for informal sector workers in Indonesia still leaves a lot of debate among our society. The basis of this employment is in Law Number 13 of 2003 concerning Manpower which is further perfected and becomes a new hope for workers in Indonesia, this hope is stated in Law Number 11 of 2020 concerning Job Creation. However, the regulation needs to comprehensively regulate the existence of informal sector workers in Indonesia. Informal workers received no guarantees or protection; many had sum-proportional wages, were found to be physically ophysically abused, and had low welfare. This study aims to analyze legal protections for informal sector workers in Indonesia. This research is normative legal research that uses a legal and conceptual approach. The data used is secondary data consisting of primary, secondary, and tertiary legal materials. Data collection techniques in this study were carried out with a review literature study and then analyzed with a qualitative descriptive method. This study's results show that a legal vacuum (rechtsvacuum) regulates the existence of informal sector workers in Indonesia. It is inherent that informal sector workers receive more attention from the government as they are the largest group of workers in Indonesia. If analyzed with 'triadism law' theory, the current legal regulations in Indonesia are considered not to have fulfilled the elements of the purpose of law itself. Therefore, with that in mind to ensure the rights of informal sector workers, it is necessary to have clear rules and guarantee workers' rights including health insurance guarantees, legal umbrellas, environmental empowerment, welfare, and social protection.